Non-Abelian gauge invariance from dynamical decoupling - Kasper, Valentin; Zache, Torsten Victor; Jendrzejewski, Fred; Lewenstein, Maciej; Zohar, Erez (Physical review, 2023)
Lattice gauge theories are fundamental to such distinct fields as particle physics, condensed matter or quantum information theory. The recent progress in the control of artificial quantum systems already allows for studying Abelian lattice gauge theories in tabletop experiments. However, the realization of non-Abelian models remains challenging. Here, we employ a coherent quantum control scheme to enforce non-Abelian gauge invariance, and discuss this idea in detail for a one-dimensional SU(2) lattice gauge system. We comment on how to extend our scheme to other non-Abelian gauge symmetries and higher spatial dimensions. Because of its wide applicability, the presented coherent control scheme provides a promising route for the quantum simulation of non-Abelian lattice gauge theories.
Gesehen am 13.05.2023